FLCN Regulates HIF2α Nuclear Import and Proliferation of Clear Cell Renal Cell Carcinoma - Zhao, Xuyang; Ma, Yadong; Cui, Jie; Zhao, Haiyang; Liu, Lei; Wang, Yueyuan; Min, Pengxiang; Zhang, Lin; Chen, Yongchang; Du, Jun; Zhang, Yujie; Gu, Luo (Frontiers in Molecular Biosciences, 2020)
Aims and hypothesis: To explore the specific molecular mechanism of FLCN-induced proliferation, migration and invasion in clear cell renal cell carcinoma (ccRCC), and to investigate the relationship of FLCN and HIF2α. Folliculin (FLCN) was identified as a tumor suppressor gene. Its deletions and mutations are associated with a potential risk of renal cancer. At present, the specific molecular mechanism of FLCN-induced proliferation, invasion and migration in ccRCC remains elusive. Methods: Cell proliferation was measured by Flow cytometry analysis, cell migration and invasion were measured by wound healing assay and Matrigel invasion assay. Expression of FLCN, HIF2α, MMP9 and p-AKT were examined by Western blotting. Cells were transfected with plasmids or siRNA to upregulate or downregulate the expression of FLCN. Immunofluorescence microscopy was carried out to display HIF2α location. We also determined the correlation of FLCN and HIF2α in human renal cancer samples. Results: FLCN was combined with HIF2α in renal tubular epithelial and cancer cells, and it effectively alleviates the deterioration of renal cancer cells by degrading HIF2α. Silencing of FLCN showed promoted HIF2α protein expression via PI3K/mTORC2 pathway, which in turn led to an increase in downstream target genes Cyclin D1 and MMP9. Moreover, interfering with siFLCN advanced the time of HIF2α entry into the nuclears. Conclusions: Our study illustrated that FLCN could be a new therapeutic target in ccRCC. FLCN combined with HIF2α and identified a novel PI3K/mTORC2/HIF2α signaling in ccRCC cells.